SELF-PERCEPTION OF INFORMATION TECHNOLOGY SKILLS OF PRE-SERVICE TEACHERS FROM THE POINT OF VIEW OF THEIR YEAR IN THE PROGRAM: Received: 7th September 2025, Revised: 27th June 2026, Accepted: 7th July 2026, Date of Publication: 10th July 2026 - Moncef Bari; Phu Chi Hoa (PUPIL: International Journal of Teaching, Education and Learning, 2026)
We present the results and analysis of a survey on the information technology skills of prospective teachers of different teaching programs, having different paths in their programs. These students belong to the Faculty of Pedagogy of Dalat University (Vietnam) and are intended to become teachers in secondary and high schools. These students have no academic IT training in their curriculum, so the objectives of this survey were (1) to find out their self-perception about the IT skills they use almost every day but without a specific course, and (2) to identify specific profiles according to the different academic progress and to make a comparison between them. The survey was conducted through the Internet, and the answers were anonymous. The questions were focused on their self-perception of their skills regarding media (images, sounds, and videos) and website editing. Students originated from different programs (biology, chemistry, English, History, Literature, maths, and physics) and the representation according to their academic progress (from the first year to the fourth and last year in their bachelor's) is rather balanced, except for the 4th year: first year: 15 answers, second year: 18, third year: 14, and fourth year: 23. The survey allowed us to identify the global self-perception for all the students and for each one of the 4 years of their bachelor's, notwithstanding the program to which they belong.